(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the theoretical and practical aspects of professional practice in determining the professional and personal qualities of future teachers requiring the development of their creative abilities, its improvement and reform, the pedagogical and psychological aspects of the development of requirements that significantly change the professional activity and supplement it with new content.